Long-term effects of early-life caregiving experiences on brain-derived neurotrophic factor histone acetylation in the adult rat mPFC - Blaze, Jennifer (Stress, 2015)
Infant-caregiver experiences are major contributing factors to neural and behavioral development. Research continues to indicate that epigenetic mechanisms provide a way in which infant-caregiver experiences affect gene activity and other downstream processes in the brain that influence behavioral development. Our laboratory previously demonstrated in a rodent model that exposure to maltreatment alters methylation of DNA associated with the brain derived neurotrophic factor (bdnf) and reelin genes as well as mRNA of key epigenetic regulatory genes in the medial prefrontal cortex (mPFC). In the current study we characterized patterns of histone acetylation at bdnf and reelin gene loci after our caregiver manipulations. Using a within-litter design (n=8–10/group from 8 litters), pups were exposed to adverse (maltreatment condition: exposure to a stressed caregiver) or nurturing (cross-foster condition: exposure to a nurturing caregiver) caregiving environments outside the home cage for 30 minutes each day during the first postnatal week. Remaining pups in a litter were left with the biological mother during each session (providing normal care controls). We then used chromatin immunoprecipitation (ChIP) and quantitative RT-PCR to measure histone 3 lysine 9/14 acetylation at bdnf exons I and IV and the reelin promoter in the adult mPFC. Maltreated females had decreased acetylation at bdnf IV, while neither males nor females exhibited histone acetylation alterations at bdnf I or the reelin promoter. These data demonstrate the ability of maltreatment to have long-term consequences on histone acetylation in the mPFC, and provide further evidence of the epigenetic susceptibility of bdnf IV to the quality of infant-caregiver experiences.